Verbal Suggestion Modulates the Sense of Ownership and Heat Pain Threshold During the “Injured” Rubber Hand Illusion - Tanaka, Tomoya; Hayashida, Kazuki; Morioka, Shu (Frontiers in Human Neuroscience, 2022)
The appearance of the self-body influences the feeling that one’s body belongs to oneself, that is, a sense of ownership (SoO) and pain perception. This can be identified by measuring the SoO and pain thresholds after performing the rubber hand illusion (RHI) with an injured rubber hand. The generation of SoO is thought to be caused by multisensory integration of bottom-up factors (vision, proprioceptive, and touch), and by top-down factors, such as the context effect. The appearance is one of the context effects which may become more effective when used simultaneously with other context effects (e.g., verbal suggestion). However, in the RHI, when appearance and other context effects are used simultaneously, the effect is unclear. In this study, we attempted to identify the influence of verbal suggestion on the SoO and heat pain threshold (HPT). As a preliminary step, in Experiment 1, the “normal” rubber hand and “penetrated nail” as injured rubber hand were used to clarify the context effect with appearance alone during RHI (synchronous/asynchronous), which was conducted within-subjects. In Experiment 2, we only used the “penetrated nail” rubber hand to clarify the context effect with verbal suggestion and appearance during RHI. We randomly classified participants into two suggestion groups (“fear” and “no-fear”). The RHI (synchronous/asynchronous) was conducted for each group. In each experiment, the effect of each condition was assessed by subjective measures of SoO, such as questionnaire, and objective measures of SoO, such as proprioceptive drift and electrodermal activity. Following RHI in each condition, HPT was measured. The main finding was that, in the synchronous condition, the “penetrated nail” appearance with “fear” verbal suggestion modulated questionnaire and HPT, but not electrodermal activity. We conclude that the context-included multisensory integration affected the subjective factors because it contains a higher cognitive process by verbal suggestion.